Effect of Simargaol - Gaol (Aglaonema Modestum Schott Ex Engl) Leaf Extract on Serum HDL, LDL and Triglyceride Levels of Rats Fed High-Fat Feed - Gulo, Kristin Wulan Liberti Vivanis; Riris, Ida Duma; Roza, Destria; Nainggolan, Bajoka; Juniar, Anna (PT FORMOSA CENDEKIA GLOBAL, 2024)
Cholesterol in the body is divided into three parts, namely Low Density Lipoprotein (LDL) High Density Lipoprotein (HDL) and Triglycerides. Excessive cholesterol in the blood can cause hypercholesterolemia. The Simargaolgaol plant (Aglaonema modestum Schott ex Engl) is one of the plants that people use as traditional medicine to cure various types of diseases. This study aims to analyze the effect of administering simargaolgaol leaf extract on reducing cholesterol levels in male Wistar rats fed a high-fat diet. This study used a Completely Randomized Design (CRD) consisting of 6 groups, namely K0+ (Normal Group), K0- (Negative Control), K+ (Positive Control given simvastatin), varying doses 100 mg/KgBW, 200 mg/KgBW, 300mg/KgBW. The data obtained was analyzed using One way Anova statistical analysis with SPSS for Windows software. The data that has been analyzed has a significant value of p<0.05, which means that administration of ethanol extract of simargaolgaol leaves (Aglaonema modestum Schott ex Engl) shows an effect on reducing cholesterol in the blood. The conclusion of this research is that the ethanol extract of simargaolgaol (Aglaonema modestum Schott ex Engl) leaves has anti-cholesterol activity at a minimum dose of 300 mg/KgBW.